Answer:
<h2>(2x - 3y)(4x - y) = 8x² - 14xy + 3y²</h2>
Step-by-step explanation:
Use FOIL: <em>(a + b)(c + d) = ac + ad + bc + bd</em>
(2x - 3y)(4x - y) = (2x)(4x) + (2x)(-y) + (-3y)(4x) + (-3y)(-y)
= 8x² - 2xy - 12xy + 3y²
<em>combine like terms</em>
= 8x² + (-2xy - 12xy) + 3y² = 8x² - 14xy + 3y²
Answer:
1 1/12
Step-by-step explanation:
3/4 + 1/3
Get a common denominator of 12
3/4 * 3/3 = 9/12
1/3 * 4/4 =4/12
9/12 + 4/12
13/12
12/12 + 1/12
1 1/12
I think it’s 17% i might be wrong
I think your answer would be 4,000
Add the 7 and 4, which =11.
multiply times the 5, =55
and 20-55= -35